2018
DOI: 10.1080/02640414.2018.1465724
|View full text |Cite
|
Sign up to set email alerts
|

Excelling at youth level in competitive track and field athletics is not a prerequisite for later success

Abstract: Enhancing our understanding of athlete development would be valuable for coaches, parents and administrators to set realistic performance expectations and to advance youth sport policy. To this end, a database of track and field performances was examined. Records of 134,313 performances by athletes aged between 12 and 35 years in sprinting, throwing, jumping and middle distance events were analysed. Results revealed that a minority (Male, 9%; Female, 13%) of top 20 ranked senior athletes were also ranked in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 32 publications
9
47
1
4
Order By: Relevance
“…If we do not discuss here findings about any particular swimmers for confidentiality concerns, we can highlight some points that seem interesting to swimming experts. First, as mentioned in [3,24], it seems difficult to precisely detect young talents before 16 years old because of the fast evolution before this age. One can observe between 14 and 16 years old a huge decrease of the value of the derivatives and thus of the speed of progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we do not discuss here findings about any particular swimmers for confidentiality concerns, we can highlight some points that seem interesting to swimming experts. First, as mentioned in [3,24], it seems difficult to precisely detect young talents before 16 years old because of the fast evolution before this age. One can observe between 14 and 16 years old a huge decrease of the value of the derivatives and thus of the speed of progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it appeared in several studies that performance at young ages provides in itself a poor predictor of the future competition results [3]. Only a small portion of elite athletes before 16 years old remains at a top level of performance later [24]. It thus seems clear that the classical strategy, which consists of training intensively in specific structures only best performers of a young age range, reaches its limits.…”
Section: Detection Of Young Athletesmentioning
confidence: 99%
“…Gullich (2014) found an average annual turnover rate of 24.5% in all German youth elite football academies, with a probability of not being in a national age group programme 5 years after starting at above 70%. In athletics, recent research has shown that only 9% of males and 13% of females ranked in the top 20 as UK senior athletes were ranked within the top 20 as under 13 s (Kearney and Hayes, 2018). This trend is also present across Olympic sports such as swimming, volleyball and judo where <30% of junior internationals progressed to compete internationally at senior level (Barreiros et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from several endurance sports shows elite senior athletes tend to specialize at a later age, and participate in a diverse range of sports during their earlier years (26,60). Recent work has also shown that very few middle-distance runners ranked in the UK top 20 in the under-13 and under-15 age-groups experience success as senior runners (43).…”
Section: Timing Of Specialization and Long-term Athlete Developmentmentioning
confidence: 99%